Is soil an organic carbon sink or source upon erosion, transport and deposition? - Liu, Lin; Zhang, Qinghui; Liu, Qianjin; Li, Zijun (European journal of soil science, 2023)
Soil may be a carbon source or sink under the effect of sediment and soil organic carbon (SOC) erosion, transport and deposition. Partial SOC processes to determine whether soil subjected to water erosion is a carbon sink or source have not been clarified but are essential for increasing and predicting SOC storage. In this review, the associations between SOC mineralization, stability and stock at erosion sites, in transported sediments and at deposition sites are clarified. An overview is given for possible determination standards that define soil carbon sinks and sources. Methods for enhancing SOC sequestration and suggestions for improving SOC prediction are also presented. Particle transport is an important intermediate process that determines the material base for SOC stability and sequestration in each erosion and deposition element. When subject to water erosion, a high probability of SOC physical stabilization and a thick soil layer are essential for soil to function as a SOC sink. Sediment transport weakens SOC physical protection in eroded areas but can promote aggregation factors at deposition sites in some cases while increasing the depth of SOC in the soil. In this circumstance, a good soil environment for plant growth facilitates the occurrence of carbon sinks. A concept for critical erosion intensity is proposed to understand SOC sink determination; the concept is presented as the volume of soil erosion per square kilometre (m3 km−2) for which the maximum reduction in vegetation cover or plant biomass still permits plants to provide enough organic matter to compensate for erosion‐induced SOC loss. If erosion intensity is higher than critical erosion intensity at the erosion site, soil degradation is obvious, and soil is presented as an OC source, and vice versa. Finally, the SOC burial method for increasing the soil carbon storage amounts in regions with thick soil layers is presented to explore the SOC sequestration potential in deep soil. The factors considered for SOC prediction should vary with research scale. We hope our review will have direct implications for the modelling of SOC dynamics under water erosion on both slopes and at large scales. Highlights Changes in soil texture and soil thickness greatly affect the amount of SOC storage at erosion and deposition sites. Selective transport of soil materials or chemical elements promotes soil aggregation. Possible standards that define soil carbon sinks and sources and suggestions for improving SOC prediction are presented. SOC burial may be a good method for increasing C storage amounts in regions with thick layers of fine soil.